Weight loss in conservative treatment of obesity in women is associated with physical activity and circadian phenotype: a longitudinal observational study - Fárková, Eva; Schneider, Jakub; Šmotek, Michal; Bakštein, Eduard; Herlesová, Jitka; Kopřivová, Jana; Šrámková, Petra; Pichlerová, Dita; Fried, Martin (Biopsychosocial medicine, 2019)
Introduction: The study investigates the association between circadian phenotype (CP), its stability (interdaily stability - IS) and physical activity (PA) in a weight loss (WL) programme. Methods: Seventy-five women in WL conservative treatment (BMI ≥ 25 kg/m2) were measured (for about 3 months in between 2016 and 2018) by actigraphy. Results: We observed a difference in time of acrophase (p = 0.049), but no difference in IS (p = 0.533) between women who lost and did not lose weight. There was a difference in PA (mesor) between groups of women who lost weight compared to those who gained weight (p = 0.007). There was a relationship between IS and PA parametres mesor: p0.001; and the most active 10 h of a day (M10): p < 0.001 - the more stable were women in their rhythm, the more PA they have. Besides confirming a relationship between PA and WL, we also found a relation between WL and CP based on acrophase. Although no direct relationship was found for the indicators of rhythm stability (IS), they can be considered very important variables because of their close connection to PA - a main factor that contributes to the success of the WL programme. Discussion: According to the results of the study, screening of the CP and its stability may be beneficial in the creation of an individualized WL plan.